Enhanced productions of riboflavin and nisin through cocultivation of Lactococcus lactis and Lactobasillus rhamnosus - Abdul Halid, Nadrah (2024)
Microbial co-cultivation from different species of lactic acid bacteria (LAB) has the potential mean to trigger its quorum sensing to induce the production of targeted metabolites and possibly increasing its yield. The interspecies relationship between Lactococcus lactis ATCC 11454 and Lactobacillus rhamnosus ATCC 7469 were evaluated by comparing the growth profile (OD 600), specific growth rate (μmax), riboflavin yield (vitamin B2), and nisin activity (against Listeria monocytogenes and Bacillus subtilis). Fermentation was performed between the monocultures of L. lactis (LL) and L. rhamnosus (LR), and their co-culture (LL+LR). The fermentation conditions (temperature, pH, agitation, carbon and nitrogen sources, inoculation ratio and time) were varied to attain optimum bacterial growth, riboflavin and nisin yield. Subsequently, fermentation in 2.0 L stirred tank bioreactors were investigated using the combination of optimized factors in shake-flask scale. Batch fermentation was implemented in the control (C) bioreactor, while fed-batch fermentation was employed in bioreactor run 1 (B1) and run 2 (B2), with different medium flow rates of 10 mL/min and 1.6 mL/min, respectively. The most profound factors to enhance the riboflavin yield were temperature 37°C at pH 6.5, without additional glucose and yeast extract. The cell growth, nisin activity and most significantly riboflavin yield in LL+LR increased by 58% and 57% as compared to LL and LR, respectively. Furthermore, B1 was able to generate an increase of 33.5% riboflavin and 36% growth rate than C and B2. The application of bioreactor in the fermentation process resulted in a prolonged exponential phase which subsequently contributed to a longer timeframe for metabolite production. The findings from this study provided an efficient future prospect of LAB co-culture, potentially by extending riboflavin production time and increasing vitamin level in fermented foods or facilitating the production of valuable metabolites.